TINJAUAN HUKUM TERHADAP PERLINDUNGAN KONSUMEN PRODUK KOSMETIK ILLEGAL IMPOR CINA DI KOTA SEMARANG - Tri Rejeki Putri Kinasih; Muzayanah Muzayanah (Jurnal Ilmiah Dinamika Hukum, 2017)
In Semarang city suspected of many cosmetic products packaging or wrap that is circulating in the community did not provide information that is clear, both in terms of composition that does not mention the substance or the standards set by the health department, products with labels that have expired, as well as product information is misleading, particularly outstanding in the traditional markets. It is then the background for the author to take the title: "Overview of Consumer Protection Laws Against Illegal Import Chinese Cosmetic Products in Semarang". Formulation The problem in this case is (1) How are monitoring has been done by the government (BBPOM) to consumer protection in the field of cosmetic products illegally imported Chinese in Semarang? How can these obstacles to the implementation of supervision BBPOM against illegal imports of Chinese cosmetic products in the protection of consumers in Semarang? How are the remedies that have been taken by the government BBPOM to consumer protection related to the circulation of illegal imports of Chinese cosmetics in the city of Semarang The method used in this research is the method of approach to examine the rules of the applicable law, whereas the specification of the research is analytic descriptive only portray the legislation in force linked and analyzed with the theories of jurisprudence and a keadaaanatau particular object in a factual and accurate, and the data obtained will be analyzed qualitatively. The results showed that (1) Efforts to control the government has done (BBPOM) to consumer protection in the field of cosmetic products illegally imported Chinese in the city, carried out with the cooperation and coordination across relevant sectors, among others, by the District Government / City (Department of Health / Department of Industry / Department of Commerce), the National Police, as well as the Association as well as the role of the community. (2) The form of the obstacles to the implementation of supervision BBPOM against cosmetic products illegal Chinese imports in the protection of consumers in the city of Semarang, among others, actors utilize means and legal products, the perpetrator repackaging its products, the lack of public attention, the number of products containing hazardous materials, (3) Efforts the completion of which the government has done BBPOM to consumer protection related to the circulation of cosmetic illegal imports of Chinese in Semarang city is done by sanctioning criminal and administrative sanctions, but it is done through counseling, talk shows, seminars and the distribution of stickers to be vigilant and clever in choosing and using cosmetics that will be